Problems of Supporting Individual Business Initiatives in Russia ("Journal "U". Economy. Management. Finance.", 2021)
The article reviews the national project «Small and medium-sized enterprises and problems of supporting individual entrepreneurial initiative in Russia». The goals, purpose, and objectives of the project are highlighted.
Keywords: implementation; result; perspective; initiative; entrepreneurship; support; national project; small business; medium business